Oxidation behavior of 30wt.%Cr-3.75wt.%V high chromium cast iron - Wiengmoon A. (2017)
© 2016 Trans Tech Publications, Switzerland. This work focuses on the oxidation behavior of 2.4wt.%C-30wt.%Cr-3.75wt.%V cast iron in air at 1000 oC for 1-48 h with weight gain measurements taken at different times. The oxidized surfaces and cross sections were characterized by XRD, OM, SEM and EDS. It was found that the as-cast microstructure consisted of a ferritic matrix and M 7 C 3 carbide. The surface oxide scale consisted of multi-oxides and the grain size of the oxides increased with increasing holding times. XRD and SEM-EDS results revealed that the multi-oxide layer can be Cr 2 O 3 , (Fe,Cr,V) 2 O 3 and SiO 2 . After about 48 h, a continuous SiO 2 inner-layer was observed and the oxide scale tended to swell, contained pores, and became detached from the surface because of its poor adherence.